2002
DOI: 10.1063/1.1494124
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of SiO2/Si(001) interface roughness for thin gate oxides by scanning tunneling microscopy

Abstract: We studied the interface roughnesses of SiO2/Si(001) for gate oxides of 8 and 15 nm thicknesses together with RCA-treated samples by using scanning tunneling microscopy (STM). By STM observation and scaling analysis we made clear that the interface roughnesses of thermal oxides/Si substrates were similar to each other and to that of the chemical oxide/Si substrate prior to thermal oxidation; the correlation length was 23–26 nm and the rms roughness at length scales larger than the correlation length was 0.28–0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…60,61 Later experiments have hinted that the correlation length characterizing roughness may be larger. Yoshinobu et al 62 used atomic force microscopy to infer a correlation length of 15 nm, a conclusion upheld by Gotoh et al 63 using scanning tunneling microscopy, who found a correlation length of 23-26 nm. Even small amplitude rms fluctuations can result in short time scales for mixing valley-split levels, since the wave vectors of the bottoms of the two valleys correspond to very short length scales (≈ 1 Å in Si).…”
Section: Introductionmentioning
confidence: 96%
“…60,61 Later experiments have hinted that the correlation length characterizing roughness may be larger. Yoshinobu et al 62 used atomic force microscopy to infer a correlation length of 15 nm, a conclusion upheld by Gotoh et al 63 using scanning tunneling microscopy, who found a correlation length of 23-26 nm. Even small amplitude rms fluctuations can result in short time scales for mixing valley-split levels, since the wave vectors of the bottoms of the two valleys correspond to very short length scales (≈ 1 Å in Si).…”
Section: Introductionmentioning
confidence: 96%
“…For length scales larger than L = 5 nm, e.g. for image sizes larger than the average step-step separation, we observe a correlation exponent 2H~1 with a correlation length of ξ=22 ± 2 nm, similar to the long range morphology of Si(111) and thick SiO 2 films [34][35][36][37]. Another measure of the surface roughness is the root mean square (RMS) roughness.…”
mentioning
confidence: 51%
“…These measurements confirm that the second layer structure is the Pn(001) plane (ab plane) in the thin film phase, or Pn polymorph IV[9], as is commonly observed in Pn films on thick SiO 2 systems[4,13,14].The morphology observed by STM can be attributed to variations conductance variations for length scales smaller than a single terrace, and to the density of Si steps for length scales larger than a single terrace. To compare the short and long-range roughness characteristics[33][34][35], the 2D STM height-height correlation function, the STM height measurements z(r) for the atomically clean and Pn-covered UTO surfaces. The correlation functions are observed to behave as…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This was initially taken as Δ=0.3nm as this is approximately the separation of a single inter-atomic layer spacing of the silicon lattice, the rough surface being observed to vary by this amount. A range of values from 0.2nm -0.3nm has however been reported in the past [10,11]. It should be expected that the simplified, discontinuous transition of the material dielectric, representing the interface within the discretised simulation domain, would ignore the chemical width at the interface [12].…”
Section: Resultsmentioning
confidence: 96%